Southern Ocean seabird population shifts over the Holocene revealed by peat sequestration of mercury from guano - Chuxian Li; Stephen J. Roberts; Martin Grosjean; Adrien Mestrot; Martin Wille; Richard A. Phillips; Maxime Enrico; Kevin Bishop; Ulf Skyllberg; Dmitri Mauquoy; Clemens von Scheffer; Thomas Theurer; et al. (Proceedings of the National Academy of Sciences, 2026)
Monitored seabird populations have declined by up to 70% worldwide since the 1950s. Yet, data on long-term seabird population dynamics prior to the anthropogenic era are largely unknown. This limits our ability to understand future population trajectories, particularly in the Southern Ocean, where seabirds are facing multiple environmental threats. Here, we use mercury (Hg) derived from seabird guano in peatland catchments as a tracer of colony population sizes on sub-Antarctic Bird Island (South Georgia). Peat Hg flux and isotope signature results show that the first sustained seabird colonies after deglaciation were established on the island between 6800 and 6100 years ago, predating evidence for colonization on other sub-Antarctic islands by more than 1,000 y. The four subsequent periods with large local seabird populations occurred during phases of less intense Southern Hemisphere westerly winds. Our study unveils significant and repeated millennial-scale shifts in seabird abundance in response to natural climate changes, implying that the present-day increase in westerly wind intensity may lead to further declines in seabird populations in the Southern Ocean.